Pengaruh Live Streaming, Content Marketing dan Online Customer Review Terhadap Keputusan Pembelian pada Tiktok Shop (Studi Kasus pada Gen Z Kabupaten Tulungagung) - Sari, Renita; Anasrulloh, Muhammad (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to determine the influenceLive Streaming, Content Marketing and Online Customer Review to Purchase Decision at Tiktok Shop (Case Study on Gen Z in Tulungagung Regency. The method used is an associative research method using a quantitative approach. Data was collected through a questionnaire distributed to 96 Gen Z in Tulungagung Regency. The results of the analysis show that there is a significant influence fromLive Streamingon purchasing decisions, with a calculated t value of 2.513 which is greater than the t table (1.987) and a significant value of 0.014 which is smaller than 0.05. In addition, Content Marketing also has a significant negative effect on purchasing decisions, with a calculated t value of 2.671 which is also greater than the t table (1.987) and a significant value of 0.009 which is smaller than 0.05. next Online Customer Revieww hich has no influence on purchasing decisions, with a value of 1.134 which is smaller than (1.987) and a significant value of 2.60 which is greater than 0.05. Simultaneously, these three variables provide a significant contribution to purchasing decisions, with a calculated F value of 4.651 which is much larger than the F table (2.7032) and a significance value of 0.005. The results of the determination coefficient have an influence of 10.3%, while the remaining 89.7% is influenced by other variables outside the study.